Differential responses of root pattern in green gram and soybean under varying regimes of shade in a semi arid agroclimatic region - Alam, Badre; Singh, Rashmi (Indian Journal of Agroforestry, 2020)
The effects of shade on root pattern were studied in green gram (Vigna radiata L.) and soybean (GlycineÂ max L. Merill) at National Research Centre for Agroforestry, Jhansi located in a semi-arid zone of Central India. The crops were grown under three different categories of shades (33%, 50% and 75 %) in the field of separate net houses or without shade in open field. Root length and root dry weight gradually declined with increasing shade in both the crops. Similar trend was also observed in root length density. Soybean had higher root length, root dry weight and root length density than green gram in all the shade regimes. In green gram, during kharif season of 2007, root length in open field was about 42% more than in 33% shade, whereas, under 50% shade and 75% shade, the root length were about 63% and 64% lesser than in open field, respectively. Similarly, root length of soybean in open field was about 15% more than in 33% shade, whereas, under 50% shade and 75% shade, root length were about 49% and 60% lesser than in open field, respectively. Similar trend of root length was observed during kharif season of 2008. The magnitude of difference of root length between open and all the shade regimes was higher in green gram than soybean. However, specific root length (SRL) was progressively increasing with increasing shade intensity in comparison to the open grown crops. Our results Concluded that soybean showed better root growth under shade than green gram.